Dynamics of Residual Malaria Transmission and Impact on Vector Control in Bangui, Central African Republic - (:unkn) unknown (My University, 2021)
In the last decades, the scaling up of interventions against malaria vectors helped to greatly reduce the malaria-related morbidity and mortality across Africa. Yet, malaria elimination has rarely been achieved, and in the last years, a reduction of the efficacity of such measures and a recrudescence in malaria cases have been remarked. These observations highlight the limitations and/or even failures of vector control measures, such as insecticide-treated nets and indoor residual sprays, leading to a rebound in the vector population and malaria transmission. This rebound has been associated with the emergence of physiological resistance to insecticides and a change in certain behavioral traits within these vector populations, which may help maintain malaria transmission known as residual, which persists even when vector control is used effectively, and pose a challenge to the control of malaria in many parts of Africa. In this work, we studied the biting rhythms of the main malaria vectors in Bangui, Central African Republic (CAR). Despite the massive implementation of insecticide-treated nets, malaria remains a critical burden in CAR, and is the main cause of death in children. We used an innovative sampling design (non-stop 48-hour collections across the year) and a new circular statistical approach to understand the biting behavior of the main malaria vectors in Bangui. Our results revealed an unexpected and important proportion of indoor day-time biting events by the major malaria vectors Anopheles gambiae, Anopheles coluzzii and Anopheles funestus. Although indoor day-time bites have been neglected in malaria control programs, they can significantly affect vector control measures. Then, we investigated the genetic factors involved in vector behavior at the local scale. To this end, we assessed the role of the chromosomal inversion 2La in An. gambiae and An. coluzzii, the main malaria vectors in Africa. Our analysis showed that the frequency of th
Keywords: African Research